Elementos de sucesso em empreendimentos de economia solidária: teoria e realidade no contexto da coleta seletiva do lixo - Becker , Marcio (2021)
Solidarity economy ventures have expanded in Brazil and worldwide, especially in recent decades, organizing people, promoting actions and fields of action in different areas, hitherto lacking structure, observation, investments and, mainly, public policies. In this context, cooperatives and associations emerge as the main organizational and formalization models of these undertakings, normally willing to be based on initial assumptions of self-management, cooperation, participation, community engagement, democracy and collective ownership of the means of production, as these are the basic principles proposed by the available literature. However, even in the face of the warning in this same literature regarding the distortion or difficulties in the effective use of these principles, it was not known, for sure, if there would be other successful elements capable of enhancing, restructuring and even recreating previously known assumptions. In this sense, there was a research gap hitherto unexplored, which is precisely the identification of the successful elements that govern the actions and activities of solidary enterprises, in parallel with what has already been proposed in the literature, using as a basis the cooperatives and associations of selective garbage collection. Thus, the question of this research questioned whether cooperatives and associations of selective garbage collection present elements of success due to the integral observation of the basic principles proposed for projects with solidary characteristics, already proposed in the literature. From this questioning, the objectives emerged that point to the investigation of the guiding principles of solidary enterprises and their comparison with the perceived success elements, characterization of the enterprises and the identification of the existing success elements. Therefore, this research was characterized as being of an applied, exploratory and descriptive nature, with a qualitative approach, whose field of study involved fifteen associations and cooperatives located in the fifteen municipalities of Paraná bathed by the reservoir of the Itaipu Hydroelectric Plant, in the western region of the state. After applying the data collection instrument and with the help of the Iramuteq software, it is possible to verify the individual and regional reality, as well as the proof that these projects are not supported by the basic principles proposed by the literature, but their true elements of success they point to formalization, public policies, interpersonal relationships, production, leadership, popular support and financial security. Therefore, it is concluded that the theoretical principles proposed for the effective characterization of projects with solidary characteristics are, at least in this region and in this context, being replaced and considerably rooted by the successful elements now discovered and presented.